2001
DOI: 10.1146/annurev.pharmtox.41.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics and Ion Channels: Molecular Models and Sites of Action

Abstract: The mechanisms of general anesthesia in the central nervous system are finally yielding to molecular examination. As a result of research during the past several decades, a group of ligand-gated ion channels have emerged as plausible targets for general anesthetics. Molecular biology techniques have greatly accelerated attempts to classify ligand-gated ion channel sensitivity to general anesthetics, and have identified the sites of receptor subunits critical for anesthetic modulation using chimeric and mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
240
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(251 citation statements)
references
References 134 publications
8
240
1
Order By: Relevance
“…Molecular modeling studies of alcohol-binding sites in the GABA A and glycine receptors have identified a potential site as a hydrophobic pocket formed by amino acids from the second and third transmembrane domains 6,9,[35][36][37] . The recent structure of the transmembrane domains of the Torpedo n-acetylcholine receptor (nAchR) supports this model 38 and suggests the alcohol-binding site is in a pocket between the transmembrane helices.…”
Section: Towards a "High-affinity" Alcohol Binding Sitementioning
confidence: 99%
“…Molecular modeling studies of alcohol-binding sites in the GABA A and glycine receptors have identified a potential site as a hydrophobic pocket formed by amino acids from the second and third transmembrane domains 6,9,[35][36][37] . The recent structure of the transmembrane domains of the Torpedo n-acetylcholine receptor (nAchR) supports this model 38 and suggests the alcohol-binding site is in a pocket between the transmembrane helices.…”
Section: Towards a "High-affinity" Alcohol Binding Sitementioning
confidence: 99%
“…(Zorychta and Capek 1978;Takenoshita and Takahashi 1987;Kullmann et al 1989;Miao et al 1995; In Caenorhabditis elegans, two sorts of approaches have been taken. Using supraclinical concentrations of VAs Perouansky et al 1995;Schlame and Hemmings 1995;MacIver et al 1996;Nishikawa and MacIver 2000) to produce immobilization as an anesthetic endpoint, and postsynaptic anesthetic effects ( Jones et al 1992; Morgan, Sedensky, and co-workers have isolated novel Mihic et al 1997;Patel et al 1999;Yamakura et al 2001) mutants that are VA hypersensitive or that are suppreshave been observed that might contribute to a state of sors of the VA-hypersensitive phenotype (Morgan and general anesthesia. However, establishing a causal link Cascorbi 1985; Sedensky and Meneely 1987; Morgan between VA effects in vitro and in vivo has been problemet al 1988;Morgan et al 1990; Morgan and Sedensky atic.…”
Section: Espite Longstanding Efforts Volatile Anestheticmentioning
confidence: 99%
“…Analogous studies on the GlyR have shown that the negative charge on the conserved Asp residue in the Cys-loop (Asp The complex dynamics of the nicotinicoid superfamily of receptors are also affected by the binding of other ligands. For example, the functions of these receptors are also allosterically modulated by a wide variety of anesthetics (53). Many of these volatile anesthetics and n-alcohols appear to bind in a volume-dependent manner to an interface between M1, M2, and the M3 transmembrane segments in the region thought to reside in the extracellular leaflet of the bilayer.…”
Section: Minireview: Glyr Structure and Function 19384mentioning
confidence: 99%